Indonesian Stocks’ Volatility during COVID-19 Waves: Comparison between IHSG and ISSI - Alghifary, Muhammad Syauqy; Kadji, Dzuliyati; Hafizah, Iffah (International Journal of Islamic Economics and Finance (IJIEF), 2023)
This study aims to compare Islamic and conventional stocks’ performance amid a crisis. The performance was measured by analyzing the volatility of the Indonesian Sharia Stock Index (ISSI) and the Composite Stock Price Index (IHSG) during the COVID-19 pandemic. Based on the results of the different tests using the paired t-test and Wilcoxon rank test methods, it was uncovered that the ISSI and IHSG experienced significant changes before and after discovering the first case of COVID-19 in Indonesia. Significant changes in both values were also found when the Delta variance spread. Meanwhile, when the third wave occurred due to the presence of the Omicron variant, ISSI and IHSG could move more stable and did not experience significant shocks. Then, the estimation results of the GARCH model conclude that both Islamic and conventional stocks have an immense volatility power with an identical value of 0.94 or close to 1. The volatility is also significantly influenced by the previous volatility and the squared error, representing other previous events outside the model. Moreover, the volatility in Islamic and conventional stocks is not much different, even though both stocks have different characters in the debt and income ratio. Fundamental factors also cause this high volatility in the form of shocks in several macroeconomic variables, including the rupiah exchange rate, gold prices, and world oil prices. Besides, the contagion effect that occurred during the COVID-19 crisis also contributed to the spread of systemic risk in global stock indexes on stock volatility in Indonesia.